A case report of truncus arteriosus communis and genetic counseling - Nourzad, Gholamreza (Isfahan Cardiovascular Research Center, Isfahan University of Medical Sciences, 2013)
BACKGROUND: Truncus arteriosus communis (TAC) is a rare heart disorder with the prevalence of approximately 1%, mostly in male newborns. In this disease, aorta and pulmonary artery have not been separated during fetus development and both originate jointly from left ventricle. In addition, various disorders are reported like ventricular septal defect (VSD), mitral and tricuspid valves defects, aortic septal defect (ASD), reduction of lung and lung vessels’ resistance, pulmonary hypertension, increase in heart rate, high perspiration, bad digestion, and tetralogy of Fallot. CASR REPORT: Parents of deceased patient were referred for genetic counseling after the death of third girl due to severe cardiac disorder. Cardiologist declared the disease in deceased girl as TAC based on findings along with VSD, ASD and hypoplastic aortic arch which resulted to death in the first day of birth. CONCLUSION: There was no chromosomal disorder in chromosome analysis of patient’ skin. Parents were interested to have another child, so they were referred to university's Genetic Counseling Center to become aware of their next child’s condition. This disorder is genetically heterogeneous and multifactorial and because all external factors are not recognized, the accurate estimation of risk is not possible and the probability of risk for the next child is about 10% to 20%.